1997
DOI: 10.1002/(sici)1097-0274(199702)31:2<188::aid-ajim8>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Lead levels in Maryland construction workers

Abstract: A cross‐sectional study of unionized construction workers not currently known to be performing lead work was conducted. Participants completed an interviewer‐administered questionnaire obtaining information about demographics, work history, other possible sources of lead exposure and health status (including hypertension, noise‐induced hearing loss and renal disease). Blood was then obtained via venipuncture for whole blood lead level, hematocrit and free erythrocyte protoporphyrin determination. Two hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Smoking was presented as a significant risk factor for ED by Elbendary et al (2009) in their comparison of 434 patients with ED and 272 patients as controls under 40 years old, and a negative correlation between smoking index and IIEF-5 scores of patients with ED was detected. Some studies suggested cut-off values between 20 and 30 lg dl À1 and these studies accepted lead intoxication as over these values (Murata et al, 1993;Sokas et al, 1997;Lustberg & Silbergeld, 2002;Anis et al, 2007). In our study, the mean age was under 40 years old and smoking was a risk factor for ED in both groups of patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Smoking was presented as a significant risk factor for ED by Elbendary et al (2009) in their comparison of 434 patients with ED and 272 patients as controls under 40 years old, and a negative correlation between smoking index and IIEF-5 scores of patients with ED was detected. Some studies suggested cut-off values between 20 and 30 lg dl À1 and these studies accepted lead intoxication as over these values (Murata et al, 1993;Sokas et al, 1997;Lustberg & Silbergeld, 2002;Anis et al, 2007). In our study, the mean age was under 40 years old and smoking was a risk factor for ED in both groups of patients.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have reported that elevated blood lead levels were associated with cardiovascular disease (CVD), hypertension (HT) and cerebrovascular disease (Sokas et al, 1997;Lustberg & Silbergeld, 2002). Lead exposure causes elevation in oxidative stress indicators (Hsu et al, 1997;Marchlewicz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the expansion and intensified use of training and testing lands since World War II has resulted in split set of environmental conditions. While use of these materials contributed to providing Hobbes-like security to the state and to its citizens, they also increase health risks to service personnel on the installations and to members of the general public who are exposed to pollution through transmission via the atmosphere or hydrologic systems [81]. Until the 1970s, regulation of dangerous wastes that are associated with the manufacture and use of weapons systems was limited and the result was contaminated soils, groundwater, and buildings [34,36].…”
Section: The State Uncertainty and The Environmentmentioning
confidence: 99%
“…Energy used to 81 6 Impact of Pesticides as Organic Micro-Pollutants on the Environment metabolize pesticides and other xenobiotics (foreign chemicals) is not available for other body functions and can seriously impair growth and reproduction of the organism. Energy used to 81 6 Impact of Pesticides as Organic Micro-Pollutants on the Environment metabolize pesticides and other xenobiotics (foreign chemicals) is not available for other body functions and can seriously impair growth and reproduction of the organism.…”
Section: Process Of Metabolismmentioning
confidence: 99%
See 1 more Smart Citation